Anthropogenic antibiotic resistance genes mobilization to the polar regions. Issue 1 (1st January 2016) - Hernández, Jorge; González-Acuña, Daniel
Abstract : Anthropogenic influences in the southern polar region have been rare, but lately microorganisms associated with humans have reached Antarctica, possibly from military bases, fishing boats, scientific expeditions, and/or ship-borne tourism. Studies of seawater in areas of human intervention and proximal to fresh penguin feces revealed the presence of Escherichia coli strains least resistant to antibiotics in penguins, whereas E. coli from seawater elsewhere showed resistance to one or more of the following antibiotics: ampicillin, tetracycline, streptomycin, and trim-sulfa. In seawater samples, bacteria were found carrying extended-spectrum β-lactamase (ESBL)-type CTX-M genes in which multilocus sequencing typing (MLST) showed different sequence types (STs), previously reported in humans. In the Arctic, on the contrary, people have been present for a long time, and the presence of antibiotic resistance genes (ARGs) appears to be much more wide-spread than was previously reported. Studies of E coli from Arctic birds (Bering Strait) revealed reduced susceptibility to antibiotics, but one globally spreading clone of E. coli genotype O25b-ST131, carrying genes of ESBL-type CTX-M, was identified. In the few years between sample collections in the same area, differences in resistance pattern were observed, with E. coli from birds showing resistance to a maximum of five different antibiotics. Presence of resistance-type ESBLs (TEM, SHV, and CTX-M) in E. coli and Klebsiella pneumoniae was also confirmed by specified PCR methods. MLST revealed that those bacteria carried STs that connect them to previously described strains in humans. In conclusion, bacteria previously related to humans could be found in relatively pristine environments, and presently human-associated, antibiotic-resistant bacteria have reached a high global level of distribution that they are now found even in the polar regions.